Pemberdayaan Kelompok Pendukung ASI di Wilayah Kerja Puskesmas - Siregar, Afriyana; Hartati, Yuli; Meilina, Ayu (Jurnal Penelitian dan Pengembangan Kesehatan Masyarakat Indonesia, 2023)
Abstract The first two years of human life are critical to form the foundation of optimal growth, development and health in the long term. It is therefore very important to ensure that children aged 0-2 years get optimal nutritional care. The lack of exclusive breastfeeding coverage is influenced by several things, especially the very limited number of breastfeeding counselors, the lack of optimal educational activities, socialization, advocacy and campaigns related to breastfeeding and the lack of optimal development of breastfeeding support groups (Astika, 2012). Therefore, to increase the scope of exclusive breastfeeding in the working area of the Taman Baca Health Center, a Breastfeeding Support Group (KP-ASI) was formed by empowering the surrounding community. The lowest exclusive breastfeeding coverage in Palembang city is still low, to increase exclusive breastfeeding coverage can be done by changing the knowledge and attitudes of mothers in exclusive breastfeeding for breastfeeding mothers. KP-ASI is a form of community empowerment in this case cadres who assist health workers (nutritionists) in delivering information related to exclusive breastfeeding and motivating pregnant women and lactating mothers to breastfeed their babies up to a minimum of 6-24 months. The Breastfeeding Support Group (KP-ASI) is a group formed by health care facilities and the community to support pregnant women, new mothers and breastfeeding mothers. The implementation of training for ASI support groups (posyandu cadres) has not been implemented so that training activities are needed to assist posyandu cadres in providing skills and seeing changes in cadres' attitudes to do their duties to help the community related to health information, understanding in mentoring breastfeeding mothers so that the exclusive breastfeeding target is achieved. Keywords: Breastfeeding, support groups, babies